An Investigation Of The Multiculturalism Values In Inclusive Education: The Impacts For Fostering Peaceful Environment At Bali Hati International School - Kadek Yudha Septiawan; Ni Nyoman Padmadewi; Dewa Putu Ramendra (Vifada Journal of Education, 2026)
This study investigated the integration of multicultural values in inclusive education settings to promote peaceful values and attitudes within the educational environment. The research was conducted at Sekolah Bali Hati, an international bilingual school implementing inclusive and multicultural educational practices. The study employed a mixed-methods approach combining qualitative case study and quantitative survey designs. Qualitative data were collected through semi-structured interviews, classroom observations, field notes, and document analysis involving school principals, teachers, and students. Meanwhile, quantitative data were obtained through questionnaires distributed to teachers regarding their perspectives and experiences in integrating multiculturalism into inclusive classrooms. The qualitative data were analyzed using Spradley’s Taxonomy Analysis, while the quantitative data were analyzed descriptively using mean scores and thematic coding. The findings revealed that multicultural values were integrated into teaching and learning processes through culturally responsive teaching, cooperative learning, differentiated instruction, intercultural communication, and inclusive classroom interactions. The school policies, curriculum, and co-curricular activities also supported the implementation of multiculturalism by promoting equality, empathy, respect, collaboration, and social responsibility. Furthermore, the integration of multicultural values effectively fostered peaceful values and attitudes, including tolerance, mutual respect, empathy, social cohesion, non-discrimination, and conflict resolution among students. The study also proposed an inclusive multicultural and world peace education framework designed to strengthen peaceful educational environments, enhance social cohesion, and minimize discrimination in inclusive school settings. In conclusion, the integration of multicultural values within inclusive education plays a significant role in developing peaceful attitudes and creating harmonious educational environments. This study contributes to the development of multicultural and peace education practices, particularly in inclusive primary school contexts.